4D printing of polymers: Techniques, materials, and prospects. (March 2022) - Fu, Peng; Li, Haimei; Gong, Jin; Fan, Zengjie; Smith, Andrew T.; Shen, Kuangyu; Khalfalla, Tebyan O.; Huang, Haofei; Qian, Xin; McCutcheon, Jeffrey R.; Sun, Luyi
Abstract: Since the concept of four-dimensional (4D) printing first emerged from additive manufacturing technologies in 2013, there has been growing interest from researchers worldwide to harness its benefits for advanced manufacturing and materials design. 4D printing has the potential to extend the processing of objects beyond complex geometries by giving dynamic properties to static printed structures, which can change over time. The shapes and/or properties of printed objects can change under various stimuli, including heat, light, pH, moisture, electricity, and magnetic field, and these changes can be pre-designed and well-controlled. 4D printing thus permits the creation of variable and controllable geometries by incorporating the time dimension. In recent years, the rapid technical developments in smart materials and new printing methods have greatly expanded the scope of 4D printing. This article reviews important 4D printing technologies in conjunction with the underlying polymer science and engineering. The challenges and future opportunities in 4D printing are also discussed. Graphical abstract: Image, graphical abstract